1996
DOI: 10.1097/00007890-199606150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Successful Biolistic Transformation of Mouse Pancreatic Islets While Preserving Cellular Function1

Abstract: To utilize gene therapy, we required an efficient method to transfect intact islets before their use in transplantation. The biolistic method transforms cells by bombarding them with microprojectiles coated with DNA. Once internalized, the DNA is solubilized and expressed. We used the firefly luciferase gene driven by the human cytomegalovirus immediate early promoter as a reporter construct in freshly isolated BALB/c mouse islets to compare the transfection efficiency using either the biolistic method, lipofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…We also observed recovery from RNAi in smg-2 mutants canying a sur-5::GFP transgene (Fig. 1B) (18). Thus, recovery was not specific to unc-54 RNA or to bodv wall muscles.…”
Section: A Link Between Rna Interference and Nonsense-mediated Decay mentioning
confidence: 55%
“…We also observed recovery from RNAi in smg-2 mutants canying a sur-5::GFP transgene (Fig. 1B) (18). Thus, recovery was not specific to unc-54 RNA or to bodv wall muscles.…”
Section: A Link Between Rna Interference and Nonsense-mediated Decay mentioning
confidence: 55%
“…Particle-mediated transfection, also referred to as 'gene gun' or 'particle bombardment', is another method of DNA delivery to mammalian cells used in both in vivo and in vitro applications. [61][62][63] In this relatively novel technique, also termed biolistics, DNA is adsorbed onto gold particles and administered to cells by a particle gun.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Previous ttansfection studies on islet cells using lipofection, electroporation, or biolistic techniques (Welsh et al, 1990;German, 1993;Gainer et al, 1996) showed modest and transient expression of the exogenous genes. Successful adenovirus-mediated gene transfer into islets of newbom mice or adult rats also has been described (Becker et al, 1994;Csete et al, 1995); nevertheless several important issues remain undefined, including the optimal conditions for transduction, the identity of transduced islet cells, the time-course of in vivo expression, and details of a potential anti-adenovirus immune response that could limit the expression of vectorized sequences as well as impair the long-term function of transduced islets in vivo.…”
mentioning
confidence: 99%